Updated guidelines of reporting pharmacoeconomics and health technology assessment results from 2022 ISPOR (CHEERS 2022) - M. A. Truuts; A. A. Kurilev; A. S. Kolbin (Izdatelstvo OKI, 2022)
In 2022, ISPOR released an updated checklist on economic evaluation of health care, since the latter several years have passed, the circumstances have changed, and science has progressed that it demanded fresh relevant changes. To support decision-making in accordance with the principles of evidence-based medicine, expanding participants, the involvement of as many sides as possible for more coordinated and high-quality work. The paper contains the main principles included into the ISPOR CHEERS 2022 check-list.